The New Iberia blues / James Lee Burke. - Burke, James Lee, 1936- (New York : Simon & Schuster, 2019)
The body of a woman is found near Cyrpemort Point estate. The estate is owned by Desmond Cormier an award winning Hollywood director. Robicheaux and Deputy Sean McClain are looking for answers. Neither Cormier nor his actor friend Antoine Butterworth are saying much, but Robicheaux knows better.
Keywords: Murder -- Investigation -- Fiction; New Iberia (La.) -- Fiction; Thrillers (Fiction).; Detective and mystery fiction